No internship? No problem! - Milone, Joseph P.; Archambault, MaryJo (SCHOLE: A Journal of Leisure Studies and Recreation Education, 2021)
The pandemic created obstacles for our therapeutic recreation students who could not find or participate in an in-person internship. The only viable option was to create a virtual internship experience that still met NCTRC standards for national certification. This learning activity details the steps taken to create the experience, what was successful, and lessons learned.
Keywords: dept.rec; peer-reviewed